Deep Learning Architecture based on Behavioral and Academic Perspectives for Classifying Students in a University - S. Ramanujam, Srivats; Naren, J.; Jayaseelan, Nivedha; Vijayalakshmi; Vithya, G. (International Journal of Psychosocial Rehabilitation, 2024)
Research on the academic records of students has become increasingly popular. Recent research results advocates’ prospects that a student’s lifestyle and personality can have a major impact on his/her ethos. It has become increasingly common for students studying in universities to not fully realize the potential and prospects in a professional sphere. Technology can aid students in realizing their caliber and prosper in the professional domain. In the proposed work, a system has been suggested which examines the feasibilities of the impact that personality features can have on a student’s career in addition to academic performance.